OPTIMAL CONDITIONS FOR FORMATION OF STUDENTS' CREATIVE ACTIVITY IN THE LEARNING PROCESS IN HIGH SCHOOL - V.V. Ivanova (Academy of Cognitive and Natural Sciences, 2009)
The optimal inner and outward conditions of high school students' creative activity are being considered in the article.